2003
DOI: 10.1191/0960327103ht411oa
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of curcumin against lead neurotoxicity in rat

Abstract: Curcumin (diferuloylmethane), an active ingredient of turmeric, is known to have multiple activities, including an antioxidant property, and has been suggested to be of use in treatment of several diseases. The present study has been undertaken to investigate the protective effect of curcumin against lead-induced neurotoxicity in rats. Exposure of rats to lead (50 mg/kg po) for 45 days caused an increase in lipid peroxidation (LPO) and a decrease in reduced glutathione (GSH) levels in cerebellum, corp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
69
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(85 citation statements)
references
References 20 publications
12
69
0
3
Order By: Relevance
“…Moreover, curcumin is able to decrease the number of aberrant crypt foci in an azoxymethane-induced rat colon cancer model through apoptosis induction via the mitochondrial pathway (16). Curcumin is also known for its antioxidant properties and acts as a free radical scavenger by inhibiting lipid peroxidation and oxidative DNA damage (17).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, curcumin is able to decrease the number of aberrant crypt foci in an azoxymethane-induced rat colon cancer model through apoptosis induction via the mitochondrial pathway (16). Curcumin is also known for its antioxidant properties and acts as a free radical scavenger by inhibiting lipid peroxidation and oxidative DNA damage (17).…”
Section: Discussionmentioning
confidence: 99%
“…Pb causes significant changes in oxidative stress in different brain regions, particularly in the hippocampus and cerebral cortex which are found to be more vulnerable to Pb-induced neurotoxicity (Prasanthi et al, 2010). Several mechanisms, including cholinergic dysfunction, glutamate receptor alterations, impaired antioxidant defense enzymes in the brain and enhanced oxidative stress, have been suggested to be causative factors with lead neurotoxicity (Shukla et al, 2003). Others have suggested that oxidative stress caused by lead is associated with disrupted prooxidant/antioxidant balance (Hsu & Guo, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Studies with humans show that blood lead levels, even at 10 μg/dL, may cause cognitive deficits (Shukla et al, 2003). The brain region, including hippocampus, not only plays a major role in memory and learning, but produces neurons during the process of growing.…”
Section: Research Articlementioning
confidence: 99%
“…Curcumin acts as a free radical scavenger and antioxidant, inhibiting lipid peroxidation and oxidative DNA damage (200). Curcumin inhibited PMA-mediated activation of ERK and NF-kB transcriptional activity (121).…”
Section: Curcuminmentioning
confidence: 99%